Three questions about engagement and exclusion in responsible investment. (17th August 2015) - Kolstad, Ivar
Abstract : There is a move towards more use of engagement strategies in responsible investment. This change in strategies is motivated by a number of claims about the effectiveness of engagement versus exclusion of companies from the investment universe (the set of investment objects available to an investor). This paper examines the basis for three central claims: (1) That engagement, in contrast to exclusion, does not reduce the investment universe; (2) That exclusion reduces an investor's influence on a company; and (3) That engagement with exclusion is necessarily a more effective means of influencing companies than pure exclusion. All three claims are argued to be open to challenge. It is possible that the move towards more engagement reflects bureaucratic incentives and political considerations among institutional investors, rather than arguments about the effectiveness and efficiency of engagement.